Comparison of Oncological and Surgical Outcomes of Robot-Assisted, Laparoscopic Modified Radical Hysterectomy and Laparotomy for Endometrial Cancer - Masako Ishikawa; Kentaro Nakayama; Sultana Razia; Hitomi Yamashita; Tomoka Ishibashi; Kosuke Kanno; Seiya Sato; Satoru Kyo (Clinical and Experimental Obstetrics & Gynecology, 2024)
Background: This study aimed to compare the oncologic and surgical outcomes of patients treated with robot-assisted modified radical hysterectomy (RAMRH) and total laparoscopic modified radical hysterectomy (TLMRH) for endometrial cancer (EC) with those of patients treated with abdominal modified radical hysterectomy (AMRH). Methods: We performed a retrospective analysis of 133 patients with early-stage EC who underwent different surgical approaches (RAMRH, n = 14; TLMRH, n = 94; AMRH, n = 25) between 2018 and 2021 at Shimane University Hospital. The data on clinical outcomes, including estimated blood loss, duration of surgery, duration of hospital stay, and number of dissected lymph nodes were collected from the patients’ electronic medical records. Kaplan–Meier curves were used to plot survival data, and log-rank tests were used to determine the statistical significance of differences in survival rates. Results: RAMRH showed the lowest bleeding volume (RAMRH: 95 ± 123.21 mL; TLMRH: 140.74 ± 172.60 mL; AMRH: 482.6 ± 429 mL) and shortest hospital stay (RAMRH: 6.43 ± 1.09 days; TLMRH: 7.30 ± 3.39 days; AMRH: 9.88 ± 2.65 days) among the three groups. The number of dissected lymph nodes tended to be higher in the RAMRH group than that in the TLMRH or AMRH group. The different surgical approaches did not correlate with progression-free survival and overall survival. Conclusions: Both RAMRH and TLMRH are safe, feasible, innovative, and minimally invasive surgical alternatives to AMRH for patients with EC.